Gender and work in ergonomics: recent trends. Issue 11 (2nd November 2022) - Laberge, Marie; Lefrançois, Mélanie; Chadoin, Martin; Probst, Isabelle; Riel, Jessica; Casse, Christelle; Messing, Karen
Abstract: Since the establishment of the Gender and Work Technical Committee (TC) of the International Ergonomics Association (IEA) in 2006, many researchers have addressed the role of sex and gender in ergonomics, producing a great deal of new information. This special issue aims to present new ways of viewing women's work and gender differences in work-related injury risks in an era of rapidly changing labour market configurations. It offers innovative methods for integrating sex and gender into ergonomic analysis and for designing work environments. It shares reflections on the intersection of vulnerabilities according to certain identity markers. Finally, it contributes to establishing milestones standards of practice so that the consideration of sex and gender can be more systematically modelled in ergonomics research and interventions, for example, in training ergonomists or in knowledge transfer initiatives. Practitioner summary: This editorial article provides an overview of the background and the content of the Special Issue 'Gender and Work in Ergonomics: Recent trends'.